Implikasi terhadap Status Kepemilikan Hak atas Tanah dalam Transformasi UMKM Menjadi Perseroan Terbatas Perorangan - Dewinta Sukma Wijaya; Isnaeni, Diyan (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the transformation of micro, small, and medium enterprises (MSMEs) into individual limited liability companies and the legal implications on land ownership status. The enactment of the Job Creation Law (UU Cipta Kerja) introduces substantial amendments to Law No. 40 of 2007 concerning Limited Liability Companies, particularly allowing the establishment of a company by a single founder via an online platform, without the requirement for a notarial deed or minimum capital. This regulatory simplification facilitates the formalization of MSMEs into individual PTs, enhancing legal certainty and access to financial services. However, a critical issue arises concerning land ownership: individual PTs, as legal entities, are not permitted to hold freehold title (hak milik). Land assets used for business purposes must be converted to land use rights, such as building use rights (HGB) or right to cultivate (HGU), to comply with agrarian regulations. This change may pose practical challenges for MSME owners who previously held land under personal ownership. For instance, farmers or small-scale producers using their residential land for business must navigate land status conversion procedures, which can be complex and costly. This study, through a normative juridical approach, reveals a regulatory gap that may affect the operational continuity of MSMEs post-conversion. Compared to previous literature that generally emphasizes administrative ease, this study highlights the often-overlooked implications of asset restructuring, particularly in land governance. The findings underline the need for harmonized policies that support MSMEs' transformation while safeguarding their control over productive land assets.   Penelitian ini bertujuan untuk menganalisis transformasi usaha mikro, kecil, dan menengah (UMKM) menjadi Perseroan Terbatas Perorangan serta implikasi hukumnya terhadap status kepemilikan tanah. Pemberlakuan Undang-Undang Cipta Kerja membawa perubahan signifikan terhadap Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas, khususnya dalam memperbolehkan pendirian perseroan oleh satu orang pendiri melalui sistem daring tanpa keharusan akta notaris dan modal minimum. Kebijakan ini mempermudah proses legalisasi UMKM menjadi badan hukum, memberikan kepastian hukum, serta akses yang lebih luas terhadap pembiayaan. Namun, tantangan muncul terkait kepemilikan tanah, karena badan hukum seperti PT tidak diperkenankan memiliki hak milik atas tanah. Tanah yang digunakan sebagai aset usaha harus diubah statusnya menjadi hak guna bangunan (HGB) atau hak guna usaha (HGU) sesuai dengan ketentuan agraria. Perubahan ini berpotensi memengaruhi operasional UMKM, khususnya bagi pelaku usaha yang menggunakan tanah milik pribadi untuk kegiatan bisnis, seperti petani atau produsen rumahan. Studi ini menggunakan pendekatan yuridis normatif, dan menemukan adanya celah regulasi yang dapat mengganggu keberlangsungan usaha pasca transformasi menjadi PT. Berbeda dengan penelitian sebelumnya yang lebih menekankan pada kemudahan administratif, penelitian ini menunjukkan pentingnya perhatian terhadap restrukturisasi aset, terutama dalam hal pertanahan. Temuan ini menegaskan perlunya sinkronisasi kebijakan agar transformasi badan usaha tidak justru menghilangkan kendali UMKM atas aset produktif yang dimilikinya.